Penggunaan Biofilter untuk Menghilangkan Bau pada Sludge Industri Es Krim - Abdul Aziz Setiawan; Sri Sugiarti; Hanies Ambarsari (BRIN Publishing (Penerbit BRIN), 2022)
The growing number of industries in Indonesia causes industrial waste to increase. Substances with upleasant smell from industrial waste can pollute the environment. Currently, not many people process and utilize industrial waste in the form of sludge left over from the WWTP process. The biofilter method will be very effective in handling air pollution because it has several advantages, among them are an easy and simple process, low investment and operational costs, and a relatively long operational time. The study began with the manufacture of incubation equipment and biofilter columns, testing the feasibility of the biofilter and incubation column, selecting fillers based on the results of a literature review, sampling fillers, preparing fillers, preparing samples of ice cream waste sludge from the ice cream industry in the Jababeka area, followed by analysis proximate sludge, analysis of ammonia gas in sludge with various variations of sludge weight and time, biofiltration process using coconut shell charcoal in order to obtain optimal variations in coconut shell charcoal size, then biofiltration using coconut shell charcoal briquettes with added zeolite content variations to determine the most effective filler material to remove odors. The results show that coconut shell charcoal with a particle size of 100 mesh is the most optimal biofilter filler for removing ammonia gas with an efficiency of 75% compared to a particle size of 20 mesh and 60 mesh which has an ammonia gas removal efficiency of 64% and 68%. Biofilter IV has the highest efficiency in removing ammonia gas, which is 90%.